Esgoto doméstico tratado como fonte de nutrientes no cultivo hidropônico do morangueiro - Figueiredo, Caroline Goulart (Universidade Federal de São Carlos, 2020)
With the growth of the world population and the consequent increase in demand for food, the agricultural sector will be impacted, resulting in greater consumption of water and nutrients to meet the demands of agricultural crops. Thus, the use of treated domestic sewage can be an alternative to ensure the use of nutrients and promote the rationalization and conservation of water bodies. This study aimed to compare the production, quality and nutritional status of strawberries grown in a hydroponic system using conventional nutrient solution and treated domestic sewage, seeking savings in the use of fertilizers. The experiment was carried out in an agricultural greenhouse in an NFT hydroponic system (Nutrient Laminar Flow Technique) with three treatments: (TA) consisting of drinking water and chemical fertilizers, (TRA) reused water supplemented with chemical fertilizers and (TR) drinking water. reused. Each treatment consisted of four cultivation benches, a motor pump system, timer and 500 L container for storage of nutrient solution. In each bench, four hydroponic profiles with capacity for 12 plants were used, totaling 48 plants per bench and 192 per treatment. The benches were divided into four randomized blocks. The nutrient content of the reused water was compared to the conventional nutrient solution, the amount of nutrients used in the treatments, the microbiological quality of the fruits, the nutritional status of the plants and the quantitative and qualitative aspects of the fruits. The TR treatment showed a significant difference when compared to the others, with visual symptoms of nutritional deficiency in the plants, lower productivity, more acidic fruits and smaller diameter. The content of soluble solids was not altered by the treatments, as well as the microbiological quality of the fruits, which did not indicate the presence of Escherichia coli. The use of reused water to compose the nutrient solution made it possible to obtain savings of 33% in chemical fertilizers in the TRA treatment, compared to TA. The reused water when supplemented meets all the parameters of the strawberry culture, being equivalent to the cultivation with conventional nutrient solution.
Treated domestic sewage as a source of nutrients for strawberry under hydroponic cultivation
Keywords: Fragaria ananassa x dusch; NFT; Água de reúso; Cultivo de hortaliças; Reused water; Vegetables cultivation; CIENCIAS AGRARIAS::ENGENHARIA AGRICOLA::ENGENHARIA DE AGUA E SOLO